2012
DOI: 10.1159/000336395
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sleep-Wake Sensitivity of Gonadotropin-Releasing Hormone Secretion to Progesterone Inhibition in Early Pubertal Girls

Abstract: Context: Early pubertal luteinizing hormone (LH), and by inference gonadotropin-releasing hormone (GnRH), pulse secretion is marked by high nocturnal but low daytime frequency; however, the underlying mechanisms remain unclear. Plasma concentrations of progesterone, the major regulator of GnRH frequency in women, increase in the early morning in early pubertal girls and may help slow daytime GnRH frequency. Objective: To evaluate the effect of progesterone on LH pulse frequency in early to mid-pubertal girls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
0
13
2
Order By: Relevance
“…In the overnight studies, DEX abolished the previously observed early morning increases of free T and P4 levels in early pubertal girls and in late pubertal girls, respectively, implying an adrenal (ACTH-dependent) source [ 12 , 13 ]. T and P4 are important regulators of gonadotropin-releasing hormone (GnRH) pulsatility with elevated T concentrations impairing P4 inhibition of GnRH pulses and P4 exhibiting day-night differences in inhibitory effects during puberty [ 21 , 22 ]. Thus, we hypothesize that diurnal changes in concentrations of P4 and T may contribute to diurnal changes of pulsatile GnRH release during puberty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the overnight studies, DEX abolished the previously observed early morning increases of free T and P4 levels in early pubertal girls and in late pubertal girls, respectively, implying an adrenal (ACTH-dependent) source [ 12 , 13 ]. T and P4 are important regulators of gonadotropin-releasing hormone (GnRH) pulsatility with elevated T concentrations impairing P4 inhibition of GnRH pulses and P4 exhibiting day-night differences in inhibitory effects during puberty [ 21 , 22 ]. Thus, we hypothesize that diurnal changes in concentrations of P4 and T may contribute to diurnal changes of pulsatile GnRH release during puberty.…”
Section: Discussionmentioning
confidence: 99%
“…LH pulses were identified using the computer algorithm Cluster 7 [ 20 ]. Mean LH concentration and pulse frequency (interpulse interval) were analyzed in 4-hour time blocks: 7:00 pm to 10:50 pm (represents time awake); 11:00 pm to 2:50 am and 3:00 am to 6:50 am (represents time asleep, time block values averaged for analysis) [ 12 , 21 ]. LH secretory characteristics and screening data for each pubertal-weight group (see the following section) were compared between subjects receiving DEX and historical controls using two-tailed Student t tests with unequal variance.…”
Section: Methodsmentioning
confidence: 99%
“…Of interest, Collins et al (245) reported that progesterone exerts differential inhibitory feedback on GnRH, suppressing daytime but not sleep-related secretion. T gradually increases during normal puberty (224,246) and may impair progesterone's inhibitory effect on daytime secretion.…”
Section: Effects Of Hyperandrogenemia On the Hypothalamuspituitarymentioning
confidence: 99%
“…We previously presented data suggesting that exogenous progesterone profoundly suppresses waking LH pulse frequency within 3–7 h in early pubertal girls (Collins et al. ), and a more recent study suggested that exogenous progesterone suppresses waking LH pulse frequency by 26% within 12–16 h in late pubertal girls during the late follicular phase (cycle day 6–11) (Kim et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The rapidity with which progesterone suppresses GnRH pulse frequency in human females remains unclear. We previously presented data suggesting that exogenous progesterone profoundly suppresses waking LH pulse frequency within 3-7 h in early pubertal girls (Collins et al 2012), and a more recent study suggested that exogenous progesterone suppresses waking LH pulse frequency by 26% within 12-16 h in late pubertal girls during the late follicular phase (cycle day 6-11) (Kim et al 2018). However, taken together with our previous studies (McCartney et al 2007;Hutchens et al 2016), the current study suggests that exogenous progesterone does not demonstrably inhibit LH pulse frequency within 10-14 h in normally cycling adult women studied during the follicular phase.…”
Section: Discussionmentioning
confidence: 99%